The Evolution of SlyA/RovA Transcription Factors from Repressors to Countersilencers in Enterobacteriaceae - W. Ryan Will; Peter Brzovic; Isolde Le Trong; Ronald E. Stenkamp; Matthew B. Lawrenz; Joyce E. Karlinsey; William W. Navarre; Kara Main-Hester; Virginia L. Miller; Stephen J. Libby; Ferric C. Fang (mBio, 2019)
ABSTRACT Gene duplication and subsequent evolutionary divergence have allowed conserved proteins to develop unique roles. The MarR family of transcription factors (TFs) has undergone extensive duplication and diversification in bacteria, where they act as environmentally responsive repressors of genes encoding efflux pumps that confer resistance to xenobiotics, including many antimicrobial agents. We have performed structural, functional, and genetic analyses of representative members of the SlyA/RovA lineage of MarR TFs, which retain some ancestral functions, including repression of their own expression and that of divergently transcribed multidrug efflux pumps, as well as allosteric inhibition by aromatic carboxylate compounds. However, SlyA and RovA have acquired the ability to countersilence horizontally acquired genes, which has greatly facilitated the evolution of Enterobacteriaceae by horizontal gene transfer. SlyA/RovA TFs in different species have independently evolved novel regulatory circuits to provide the enhanced levels of expression required for their new role. Moreover, in contrast to MarR, SlyA is not responsive to copper. These observations demonstrate the ability of TFs to acquire new functions as a result of evolutionary divergence of both cis-regulatory sequences and in trans interactions with modulatory ligands. IMPORTANCE Bacteria primarily evolve via horizontal gene transfer, acquiring new traits such as virulence and antibiotic resistance in single transfer events. However, newly acquired genes must be integrated into existing regulatory networks to allow appropriate expression in new hosts. This is accommodated in part by the opposing mechanisms of xenogeneic silencing and countersilencing. An understanding of these mechanisms is necessary to understand the relationship between gene regulation and bacterial evolution. Here we examine the functional evolution of an important lineage of countersilencers belonging to the ancient MarR family of classical transcriptional repressors. We show that although members of the SlyA lineage retain some ancestral features associated with the MarR family, their cis-regulatory sequences have evolved significantly to support their new function. Understanding the mechanistic requirements for countersilencing is critical to understanding the pathoadaptation of emerging pathogens and also has practical applications in synthetic biology.